Pengaruh Harga, Kualitas Pelayanan dan Fasilitas Coffee Shop terhadap Minat Konsumen Berkunjung ke Risala Kopi - Zahra, Sofhia Rahayu; Effendi, Ihsan; Sihombing, Tohap Parulian (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of price, service quality, and facilities on consumer interest in visiting Risala Kopi in Medan. Using a quantitative approach, the research involved 105 respondents who are customers of Risala Kopi. Data were collected through questionnaires and analyzed using multiple linear regression to determine the effect of each independent variable on the dependent variable. The results show that price, service quality, and facilities have a positive and significant effect on consumer interest, both partially (t-test) and simultaneously (F-test). This indicates that the better these three aspects are managed, the higher consumers’ interest in visiting Risala Kopi will be. The coefficient of determination (R²) value of 0.558 reveals that 55.8% of the variation in consumer interest can be explained by price, service quality, and facilities, while the remaining 44.2% is influenced by other factors not examined in this study, such as promotion, location, and brand image. Based on these findings, the study recommends that Risala Kopi should continuously improve price fairness, friendly and efficient service quality, and comfortable facilities such as interior design, cleanliness, and internet access. These improvements are expected to enhance competitive advantage, increase customer loyalty, and strengthen Risala Kopi’s position amid the increasingly competitive coffee shop industry in Medan